Analisis Kelayakan Usaha Home Industri Tahu di Desa Glagahwero Kecamatan Panti Kabupaten Jember - Hakim, Muhammad Luqman; Pudjiastutik, Endang Wahyu (Program Studi Agribisnis, 2024)
Jember is one of them the largest soybean producing district in Java east so many home industries Soybean processing sprung wrong the other one is in Glagahwero Village, Panti District and also on the way Home Industry those in Panti District are no longer there operating due to the increase in soybean prices and other costs. So this research aims to determine the feasibility of Home The Tofu Industry in Glagahwero Village it really deserves to be in try. Sampling method using purposive sampling because deliberately took the Home Industry Know in Glagahwero Village with criteria that has been determined by the researcher, the method this study uses descriptive with using primary and secondary data Based on the results of the analysis done Home Industry is worth it for attempted and sensitivity analysis shows that the Home Industry is sensitive to changes in interest rates